In vivo and in vitro ivacaftor response in cystic fibrosis patients with residual CFTR function: N‐of‐1 studies. Issue 4 (9th January 2017) - McGarry, Meghan E.; Illek, Beate; Ly, Ngoc P.; Zlock, Lorna; Olshansky, Sabrina; Moreno, Courtney; Finkbeiner, Walter E.; Nielson, Dennis W.
Summary: Rationale: Ivacaftor, a cystic fibrosis transmembrane conductance regulator (CFTR) potentiator, decreases sweat chloride concentration, and improves pulmonary function in 6% of cystic fibrosis (CF) patients with specific CFTR mutations. Ivacaftor increases chloride transport in many other CFTR mutations in non‐human cells, if CFTR is in the epithelium. Some CF patients have CFTR in the epithelium with residual CFTR function. The effect of ivacaftor in these patients is unknown. Methods: This was a series of randomized, crossover N‐of‐1 trials of ivacaftor and placebo in CF patients ≥8 years old with potential residual CFTR function (intermediate sweat chloride concentration, pancreatic sufficient, or mild bronchiectasis on chest CT). Human nasal epithelium (HNE) was obtained via nasal brushing and cultured. Sweat chloride concentration change was the in vivo outcome. Chloride current change in HNE cultures with ivacaftor was the in vitro outcome. Results: Three subjects had decreased sweat chloride concentration (−14.8 to −40.8 mmol/L, P  < 0.01). Two subjects had unchanged sweat chloride concentration. Two subjects had increased sweat chloride concentration (+23.8 and +27.3 mmol/L, P  < 0.001); both were heterozygous for A455E and pancreatic sufficient. Only subjects with decreased sweat chloride concentration had increased chloride current in HNE cultures. Conclusions: Some CF patients with residual CFTR function have decreased sweat chloride concentration with ivacaftor. Increased chloride current in HNE cultures among subjects with decreased sweat chloride concentrations may predict clinical response to ivacaftor. Ivacaftor can increase sweat chloride concentration in certain mutations with unclear clinical effect. Pediatr Pulmonol. 2017;52:472–479. © 2017 Wiley Periodicals, Inc.